PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN METODE SCRAMBLE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVC SD NEGERI 010 PANGKALAN KERINCI KABUPATEN PELALAWAN - Desliany Erdawati; Lazim N Lazim N; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the lowlearning outcomes of social studies of grade IVc in SD Negeri 010 Pangkalan Kerinci Kabupaten Pelalawan, KKM (success criteria) assigned in school, that is 75. The class consist of 25 students, who reached the KKM is just 7 students (28%), whereas students who have not yet reached the KKM is 18 students (72%) with average rating of class 66.6. To solve these problems then the researchers implement scramble cooperative learning model. The purpose of this research is to improve the learning achievement of social studies of grade IVc in SD Negeri 010 Pangkalan Kerinci Kabupaten Pelalawan with the implementation of the scramble cooperative learning model. The result of this research shows that the average value of basic score is 66.6 and increased in cycle I from 7.83% become 71.6. In cycle II, the average value of the students also increase 25.05% become 88.6. On a basic score of students classical success criteria of social studies is 28% (not completely). After implementation of scramble cooperative learning model on cycle 1, number of success criteria of students classical learning increased become 60% (not completely). And on cycle II, success criteria of students classical learning increased by 92% (completely). Then, the activity of the teacher on the first meeting of the cycle 1 got was 79.16% by category is enough. The second meeting was increased become 87.5% with category of good. on the first meeting of the cycle II teacher activity increased become 91.6% by category of very good. At the second meeting increased become 95.8% with the very good category. The activity of the students at the first meeting of the cycle I got was 79.16% by category of enough. The second meeting was increased become 87.5% with category of good. At the first meeting of the cycle II activity of students increased become 91.6% with category of good. At the second meeting increased become 95.8% by very good category. From this research it can be concluded that by implementation of the scramble cooperative learning model can improve students learning outcomes of social studies of grade IVc in SD Negeri 010 Pangkalan Kerinci Kabupaten Pelalawan.Keywords: Scramble Cooperative Method, Social Studies Outcomes